Interpersonal communication : - Wood, Julia T. (Cengage, 2020)
It also provides comprehensive coverage of the influence of social media and thorough discussions of the ethical challenges and choices that affect interpersonal communication. In addition, it covers such timely issues as emotional intelligence and forgiveness, interracial relationships, safe sex, ways to deal with abuse from intimates, race-related differences between conflict styles, and the power of language.